PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN15 PADANG - Ramayana, Ramayana; Rismen, Sefna; Anggraini, Villia (STKIP PGRI Sumbar, 2014)
ABSTRACT The background of this research was the lack of students motivation in teaching learning mathematics and result of students mathematics still low. The aim was to determined whether co-operative Talking Stick type toward students comprehension better than comprehension of mathematical concept by applied students conventional learning. This was an experimental research and applied random research toward subject. The population was eight grade of SMPN 15 Padang 2013 / 2014 .VIII.3 as experiment and VIII.2 as control. Instrument in this research was essay. Based on the data analysis, mean of experimental was 86,50 and control was 73,53, percentage of every indicator experimental higher than control . From the hypotheses testing got t-calculated 2,951 and t-table 1,697 , so t-calculated higher than t-table. Can concluded that students comprehension of mathematics concept using co-operative Talking Stick type better than conventional learning at the eight grade students of SMPN 15 Padang.